A bibliometric analysis of preoperative anxiety research (2001–2021) - Sun, Siyuan; Feng, Jingjing; Fu, Zhiwei; Lu, Zhengyi; Chen, Jiafeng; Hua, Mingyan; Su, Diansan; Gu, Juan (Frontiers in Pediatrics, 2023)
Recently, mental health has received increasing attention, particularly preoperative anxiety, which constitutes a bad emotional experience for surgical patients. Many experts have studied preoperative anxiety in terms of its related risk factors, interventions, and postoperative effects; however, there has been no systematic analysis of published articles. This paper presents a bibliometric review of documents related to preoperative anxiety published between 2001 and 2021. A detailed data analysis of 1,596 publications was conducted using CiteSpace and VOSviewer. Since the 20th century, the field of preoperative anxiety has gradually developed; research began around 2000 and has made a huge leap forward since 2016. Developed countries, led by the United States, were the first to conduct research, but preoperative anxiety research in developing countries like Turkey and China has gradually increased and led to an irreplaceable contribution. Intervention has remained the main topic of preoperative anxiety research, and measures have developed from premedication to the provision of education and information. Moreover, the use of advanced equipment such as virtual reality has emerged with great popularity. Based on previous research, the application of virtual reality combined with pediatric patients will become a new research direction.